The Classroom Impact of Trained Special Needs Education Teachers in Selected Schools: An Evaluation Study - Yuwono, Imam; Okech, John Baptist (Frontiers in Education, 2021)
The study, conducted between January and June 2019, sought to evaluate the impact trained teachers of special needs education had on effective provision of education for learners with disabilities and others with special needs (LwDs & OSNs). The study participants comprised special needs education teachers (N=73) and LwDs & OSNs (N=30). A descriptive cross-sectional design study design, involving qualitative approach were used for collecting data. The study focused on the critical role that the school should play in supporting LwDs & OSNs who experience barriers to learning. Open-ended questionnaires, interview guides and observations were used to collect the data. The findings reveal a variation of responses. Teachers’ qualification were found to have significant impact for LwDs & OSNs’ effective participation in class. Teaching methods, curriculum content, too, had important impact in children’s learning. Environmental set up and implementation of the relevant policies for LwDs & OSNs were also found to have impact in the classroom learning. One of the recommendations is that there is need for training and retraining teachers of special needs. Methods of teaching should be child-centred. Curriculum modification should be done regularly. Classroom environments need improved to be more disability friendly that it is at the moment. Lastly, implementation of policies on disabilities and other special needs should be carried out.